The Effect of Video-Based Education on Pregnant Women’s Commitment to Facility-Based Delivery in a Riverine Area of Indonesia - Aceptie Aceptie; Riyanti Riyanti; Yeni Lucin; Itma Annah (Health Dynamics, 2026)
Background: Choosing a safe place of delivery is a critical determinant of maternal and neonatal health outcomes, particularly in geographically isolated areas with limited access to healthcare services. Despite national efforts to increase facility-based childbirth, some pregnant women in rural settings still prefer home or non-health facility deliveries due to low health literacy, sociocultural influences, and accessibility barriers. Previous studies have mainly focused on improving maternal knowledge and birth preparedness, while evidence regarding the effectiveness of video-based education in strengthening pregnant women’s commitment to facility-based delivery remains limited. This study aimed to determine the effect of video-based education on pregnant women’s commitment to choosing delivery in health facilities in the working area of UPTD Puskesmas Rakumpit.Methods: This quantitative study employed a pre-experimental one-group pretest–posttest design involving 35 pregnant women selected through total sampling. The intervention consisted of a 4-minute and 15-second educational video played twice in one session, covering the importance of facility-based delivery, risks of non-facility births, benefits of skilled birth attendants, delivery service procedures, and birth preparedness through the Birth Planning and Complication Prevention Program (P4K). Commitment levels were assessed before and after the intervention using a structured questionnaire. Data were analyzed using the paired sample t-test with a significance level of 95% (α = 0.05).Result: The mean commitment score increased significantly from 65.1 to 99.28, with a mean difference of 34.18 points. The proportion of pregnant women committed to facility-based delivery increased from 62.1% to 100% after the intervention (p = 0.000).Conclusion: Video-based education effectively improved pregnant women’s commitment to choosing facility-based delivery. Keywords: video-based education; pregnant women; commitment; facility-based delivery; maternal health